Efektywność - wirowa równowaga rynkowa - Juzwiszyn, Jacek (Effectivity - Rotational Market Equilibrium, 2005)
While observing the development of stock market indexes in the three-dimensional space in the system (index value, volume, time) a rotational spiral curve is encountered. This curve traces cones in R3+. Orthogonal projections of this curve onto the planes going through the cone axis are two-dimensional stock market zigzags in systems (index value - time, volume - time). The shape of the orthogonal projection of the trajectory onto the plan perpendicular to the cone's axis resembles logarythmic spiral or, known from economics, so called arachnoic model formed in the system (volume - index).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 184-190